Data Types as Functions - Mayoh, Brian H. (DAIMI Report Series, 1978)
This paper introduces a new, simple definition of what a data type is. This definition gives one possible solution of the theoretical problems: when can an actual parameter of type T be substituted for a formal parameter of type T’? When can a type T’ be implemented as another type T’’? The preprint is an extended version of a paper presented at MFCS 78, Zakopane.